Leptin receptor expression on T lymphocytes modulates chronic intestinal inflammation in mice. Issue 7 (11th June 2004) - Siegmund, B; Sennello, J A; Jones-Carson, J; Gamboni-Robertson, F; Lehr, H A; Batra, A; Fedke, I; Zeitz, M; Fantuzzi, G
Abstract : Background: Leptin regulates appetite through the long isoform of its receptor in the hypothalamus. Although leptin regulates immune responses, it is still unknown whether a direct effect of leptin on lymphocytes is required. Aims: To clarify whether expression of leptin receptors on T lymphocytes modulates intestinal inflammation in mice. Methods: The model of colitis induced by transfer of CD4 + CD45RB high (RB high ) cells into scid mice was used. Wild-type (WT) or leptin receptor deficient ( db/db ) RB high cells were transferred into scid mice and development of colitis evaluated. Results: Leptin receptors were expressed on both RB high and RB low cells. Intestinal lymphocytes of mice with colitis expressed high leptin levels compared with healthy controls whereas the opposite was true for serum leptin levels. Transfer of RB high cells from db/db mice induced delayed disease compared with transfer of WT cells. A high rate of apoptosis in lamina propria lymphocytes and reduced cytokine production were observed early on in scid mice receiving db/db RB high cells. These effects were not due to the high levels of glucocorticoids present in db/db mice as administration of corticosterone to WT mice failed to reproduce this phenomenon. High expression of peroxisome proliferator activated receptor γ was observed in the colon of recipients of db/db compared with WT cells. Freshly isolated db/db RB high cells produced low levels of interferon γ. Despite delayed onset of colitis, as disease progressed differences between mice receiving WT or db/db cells were no longer apparent. Conclusions: These results suggest that leptin affects the immune response, partly by acting on the long isoform of its receptor expressed on T lymphocytes.